TLR4 Associated Signaling Disrupters as a New Means to Overcome HERV-W Envelope-Mediated Myelination Deficits - Göttle, Peter; Schichel, Kira; Reiche, Laura; Werner, Luisa; Zink, Annika; Prigione, Alessandro; Küry, Patrick (Frontiers in Cellular Neuroscience, 2021)
Myelin repair in the adult central nervous system (CNS) is driven by successful differentiation of resident oligodendroglial precursor cells (OPCs) and thus constitutes a neurodegenerative process capable to compensate for functional deficits upon loss of oligodendrocytes and myelin sheaths as it is observed in multiple sclerosis (MS). The human endogenous retrovirus type W (HERV-W) represents an MS-specific pathogenic entity, and its envelope (ENV) protein was previously identified as a negative regulator of OPC maturation—hence, it is of relevance in the context of diminished myelin repair. We here focused on the activity of the ENV protein and investigated how it can be neutralized for improved remyelination. ENV-mediated activation of toll like receptor 4 (TLR4) increases inducible nitric oxide synthase (iNOS) expression, prompts nitrosative stress, and results in myelin-associated deficits, such as decreased levels of oligodendroglial maturation marker expression and morphological alterations. The intervention of TLR4 surface expression represents a potential means to rescue such ENV-dependent deficits. To this end, the rescue capacity of specific substances, either modulating V-ATPase activity or myeloid differentiation 2 (MD2)-mediated TLR4 glycosylation status, such as compound 20 (C20), L48H437, or folimycin, was analyzed, as these processes were demonstrated to be relevant for TLR4 surface expression. We found that pharmacological treatment can rescue the maturation arrest of oligodendroglial cells and their myelination capacity and can prevent iNOS induction in the presence of the ENV protein. In addition, downregulation of TLR4 surface expression was observed. Furthermore, mitochondrial integrity crucial for oligodendroglial cell differentiation was affected in the presence of ENV and ameliorated upon pharmacological treatment. Our study, therefore, provides novel insights into possible means to overcome myelination deficits associated with HERV-W ENV-mediated myelin deficits.